Effects of low temperature drying processing on longan fruit - Thadchapong Pongsuttiyakorn; Pachareeporn trusphimai; Pitikhate Sooraksa; Pimpen Pornchaloempong (My University, 2018)
In this study, the single-stage drying in tray dryer at air temperatures of 40, 50, 60, 70 and 80°C is modelled and investigated. The longan fruits, E-dor variety, are peeled and seeded before testing. The drying rate is significantly influenced by the drying techniques and temperatures. Drying rats are initialized adjustment constant rate periods at 60 70 and 80°C. The rate of moisture removal is rapidly changed drastically during the falling rate period. The Midilli model with high R 2 and low χ 2 and RMSE is the most suitable model for predictability of longan drying. Variation rates of quality of the water activity, the shrinkage, and the browning index are also reported.
Keywords: Browning; Tray; Shrinkage; Predictability; Food Drying and Modeling